Source and succession of microbial communities and tetramethylpyrazine during the brewing process of compound-flavor Baijiu - Cheng, Wei; Lan, Wei; Chen, Xuefeng; Xue, Xijia; Liang, Huipeng; Zeng, Huawei; Li, Ruilong; Pan, Tianquan; Li, Na; Yang, Hongwen (Frontiers in Microbiology, 2024)
Pyrazines are important flavor components and healthy active components in Baijiu, which including tetramethylpyrazine (TTMP). During the brewing process, the traceability of microbial communities and the content distribution characteristics of TTMP are important for improving the quality and style characteristics of compound-flavored Baijiu (CFB). However, the traceability analysis of microorganisms in fermented grains (FG)—used in the production of CFB—lacks quantitative and systematic evaluation. In this study, the microbial communities and TTMP content of Jiuqu (JQ), Liangpei (LP), FG, and pit mud (CP) used in CFB production were characterized; further, coordinate and discriminant analyses were employed to determine differences in microbial communities. Additionally, traceability and correlation analyses were performed to reveal the origin of microbial communities in FG. The source, content, and distribution characteristics of TTMP based on the brewing process have also been discussed. The results showed that most of the bacterial and fungal communities at different levels of FG came from other sources, and the microorganisms of Cladosporium, Acetobacter, Aspergillus, Methanosarcina, and Bacillus were considered have a osculating correlations with TTMP content of FG. Taken together, this study provides insights into the origin of microbial communities in FG and the distribution characteristics of TTMP based on the CFB brewing process. The current findings are conducive for optimizing the fermentation process and improving the quality and style characteristics of CFB.